2021
DOI: 10.1111/trf.16407
|View full text |Cite
|
Sign up to set email alerts
|

Improving the donation experience and reducing venipuncture pain by addressing fears among whole‐blood and plasma donors

Abstract: Background: Fear of blood donation is implicated in vasovagal reactions, donor recruitment, and retention. This study examined the extent to which fear among donors is associated with various donor outcomes in an Australian sample, and whether fear can be addressed on-site to reduce adverse reactions and improve the donation experience. Study design and methods: Six hundred and sixty-four donors (age M = 33.4, SD = 12.7; 55% female) participated in a two-center, pragmatic, parallel group, individually randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…On the one hand, this may be accomplished by offering the level of payment that they deemed necessary to motivate them. On the other hand, these prospective donors may also be willing to donate for less money, and perhaps even no payment, if we help to alleviate their fear and anxiety and increase their confidence 14,24 . In addition, we could work toward similar outcomes by activating demonstrated motivators such as warm glow and anticipated regret 25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, this may be accomplished by offering the level of payment that they deemed necessary to motivate them. On the other hand, these prospective donors may also be willing to donate for less money, and perhaps even no payment, if we help to alleviate their fear and anxiety and increase their confidence 14,24 . In addition, we could work toward similar outcomes by activating demonstrated motivators such as warm glow and anticipated regret 25 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, these prospective donors may also be willing to donate for less money, and perhaps even no payment, if we help to alleviate their fear and anxiety and increase their confidence. 14,24 In addition, we could work toward similar outcomes by activating demonstrated motivators such as warm glow and anticipated regret. 25 Although an important strength of the present study was recruitment of both donors and non-donors from two different sources, as with any study there are also limitations that must be considered when interpreting the findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the early phases of COVID-19, there was only an incidence of reduction in blood supply. 16 How to Increase Blood Supply in Blood Banks?…”
Section: Outbreaks Of Covid-19 Lower Blood Supplymentioning
confidence: 99%
“…A previous meta-analysis of randomised trials has, however, shown that there is limited evidence to support water loading or AMT,(16-18) because previous studies have typically involved small sample sizes; nonrepresentative populations; non-robust outcomes de nitions; and sub-optimal randomisation methods. These concerns apply even more sharply to the sparser evidence available on other interventions used by some blood services, including isotonic drinks (19)(20)(21) prolongation of post-donation recovery time, and psychosocial educational materials (22,23). Hence, blood services need more robust evidence to help shape and inform their currently diverse approaches to prevent VVRs.. To evaluate the effects of four interventions for the prevention of VVRs among whole blood donors, we have designed the Strategies to Improve Donor Experiences (STRIDES) trial, a large cluster-randomised trial across all sites of the national blood service in England (National Health Service Blood and Transplant [NHSBT]).…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%